Analiza wpływu ustawy o infrastrkutrze informacji przestrzennej na proces tworzenia włączania do infrastrkutury informacji przestrzennej miejscowych planów zagospodarowania przestrzennego = Impact analysis of the inspire directive on land-use planning publication and development - Izdebski, Waldemar; Malinowski, Zbigniew (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The INSPIRE Directive went into force in May 2007 and it resulted in changing the way of thinking about spatial data in local government. Transposition of the Directive on Polish legislation is the Law on spatial information infrastructure from 4 March 2010., which indicates the need for computerization of spatial data sets (including land-use planning).
Keywords: planowanie przestrzenne; GIS; INSPIRE Directive; infrastruktura danych przestrzennych; usługi sieciowe; land-use planning; spatial data infrastructure; web services